Fa'aliyatu Namudzaji al-Ta'allumi al-Qaimi 'ala al-Masyari' fi Tanmiyati Maharati al-Kitabah lada Thalabati Qismi Ta'limi al-Lughati al-'Arabiyati fi Jami'ah Jambi fi Muqarrari Mabadi' al-Insya' - Abdul Muid; Firman Afrian Pratama (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2023)
This study aims to reveal a project-based learning model in improving the writing skills of students (maharah al-Kitabah) of the Arabic language education study program at Jambi University in the Mabadi 'al-Insya' course. The subjects in this study were students of the 3rd semester Arabic language education study program consisting of two classes R001 and R002. Data were collected through observation, and interviews. Performance instruments, observation guidelines, and interview guidelines were used to collect data. Qualitative data analysis will be used to analyze the results of this study. The results showed that 1) the project-based learning model was applied to the Mabadi' al-Insha' course in several stages. This stage includes determining the topic or theme of writing, determining reference sources, collecting material (writing rules) and mufradat (vocabulary), sentence preparation, discussion with teammates, and presentation in front of other teams. 2) In general, students have the ability to create sentences that are based on the elements of the sentence they have learned.